E-mail messages can be effective to make the health education activity of family pediatricians more effective - Russo Krauss, P.; Maione, L.; Cione, I. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Not all family pediatricians carry on their health education tasks constantly and they do not often use effective communication strategies. To deal with this situation it is useful to find ways that are easy to implement, reproducible in the most diverse contexts and that can be accepted even by the least motivated pediatricians. We have been experimenting a training method, based on sending a series of e-mail messages, assessing their feasibility and effectiveness. Study design. Experimental approach. Methods. The intervention consisted of sending 21 email to 141 family pediatricians. In order to assess the intervention effectiveness, we first select randomly 20 pediaticians out of the 141 and before the intervention we interviewed in their offices 400 parents of 2-14 years-old children (20 parents for each of the 20 family pediatricians); similary 5-6 months after the intervention, we selected randomly other 20 pediatricians and interviewed 355 parents. The emails mentioned the 5 A’s model as well as the motivational interview, the model of the stages of change and the counseling techniques. They also enclosed communication material to be reproduced and given to the parents, as well as recommendations and guidelines. Five messages contained self-assessment tests. Results. Following the intervention, out of 26 questions asked to mothers, there was a significant improvement in the response to 10 questions and a worsening in the response to a single question. The overall difference between before and after the intervention is very significant (p <0.0001). Conclusions. The intervention was proved to be very effective and easily reproducible. It is necessary to confirm these findings with further studies based on the use of a control group too. It appears to be the first time that email messages are sent in order to train family pediatricians on the behavior change counseling.